Bubble-Induced Color Doppler Feedback Correlates with Histotripsy-Induced Destruction of Structural Components in Liver Tissue - Macoskey, Jonathan J. (Ultrasound Med Biol, 2018)
Bubble-induced color Doppler (BCD) is a histotripsy therapy monitoring technique that uses Doppler ultrasound to track the motion of residual cavitation nuclei that persist after the collapse of the histotripsy bubble cloud. In this study, BCD is used to monitor tissue fractionation during histotripsy tissue therapy, and the BCD signal is correlated with the destruction of structural and non-structural components identified histologically to further understand how BCD monitors the extent of treatment. A 500-kHz, 112-element phased histotripsy array is used to generate approximately 6×6×7 mm lesions within ex vivo bovine liver tissue by scanning over 219 locations with 30–1000 pulses-per-location. A 128-element L7-4 imaging probe is used to acquire BCD signals during all treatments. The BCD signal is then quantitatively analyzed using the time-to-peak rebound velocity (t(prv)) metric. Using the Pearson correlation coefficient (PCC), the t(prv) is compared to histological analytics of lesions generated by different numbers of pulses using a significance level of 0.001. Histological analytics in this study include viable cell count, reticulin-stained type III collagen area, and trichrome-stained type I collagen area. It is found that the t(prv) metric has a statistically significant correlation with the change in reticulin-stained type III collagen area with a PCC of −0.94 (p < 0.001) indicating that changes in BCD are more likely due to destruction of the structural components of tissue.